2024
DOI: 10.3390/su16072967
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Turbulence Intensity on Aerodynamic Loads of Floating Wind Turbine under Wind–Wave Coupling Effect

Wenxin Tian,
Qiang Shi,
Lidong Zhang
et al.

Abstract: This study first employs TurbSim and OpenFAST (Fatigue, Aerodynamics, Structures, Turbulence) programs for secondary development to comprehensively model the NREL-5MW semi-submersible wind turbine and OC4-DeepC wind floating platform with wind–wave interaction. Next, we investigate the dynamic response of floating wind turbines under the complex coupling of turbulent winds and irregular waves. Turbulent wind fields were simulated using the IEC Kaimal model with turbulence intensities of 5% and 20%. Additionall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…Several studies have been conducted on turbulence intensities, such as turbulence intensities such as [ 12 ] used LiDAR to study the mean wind shear [ 13 , 14 ], classified the turbulence intensities into low level, medium, and extreme or high [ 15 , 16 ], studied the impact and how it causes a reduction in power performance [ 14 ]; obtained 23–42 % power reduction from the turbulence effect [ [17] , [18] , [19] ], showed that turbulence intensities can lead to power output deviation from overestimate or underestimate depending on wind characteristics. Tian et al, 2024 [ 17 ] presented discrepancies in power curves attributed to the effects of turbulence intensity. Jiao et al, 2013 [ 20 ] It was found that increasing turbulence intensities led to changes in vibration, load, and fatigue of the wind turbine nacelle.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted on turbulence intensities, such as turbulence intensities such as [ 12 ] used LiDAR to study the mean wind shear [ 13 , 14 ], classified the turbulence intensities into low level, medium, and extreme or high [ 15 , 16 ], studied the impact and how it causes a reduction in power performance [ 14 ]; obtained 23–42 % power reduction from the turbulence effect [ [17] , [18] , [19] ], showed that turbulence intensities can lead to power output deviation from overestimate or underestimate depending on wind characteristics. Tian et al, 2024 [ 17 ] presented discrepancies in power curves attributed to the effects of turbulence intensity. Jiao et al, 2013 [ 20 ] It was found that increasing turbulence intensities led to changes in vibration, load, and fatigue of the wind turbine nacelle.…”
Section: Introductionmentioning
confidence: 99%